Putusan Mahkamah Agung Nomor 6 P/Hum/2020 Tentang Persyaratan Pencalonan Kepala Daerah Dalam Perspektif Fiqh Siyasah - Moh. Irfan; Amirullah Fikri (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2022)
This paper focuses on Supreme Court Decision No: 6 p/hum/2020 regarding the requirements for nomination of regional heads in the perspective of Fiqh Siyasah. The data used in this study were collected using library research methods. The results of this study conclude that the Supreme Court Decision No: 6 P/HUM/2020 grants the applicant's request in its entirety and cancels the provisions of Article 4 Paragraph (1) Letter P Number 2 PKPU Number 3 of 2017 relating to the limitation of the political rights of the Deputy Governor who to run for regent/mayor. In addition, in siyasa fiqh it is emphasized that a law must be fair and must accommodate the privileges and rights of the community, one of which is the privilege of political rights based on equal rights which is also regulated in Law no. 39 of 1999 concerning Human Rights Articles 15 and 43.